Toxoplasmosis as a cause of life‐threatening respiratory distress in a dog receiving immunosuppressive therapy. Issue 5 (2nd April 2019) - Pepper, Amy; Mansfield, Caroline; Stent, Andrew; Johnstone, Thurid
Key Clinical Message: Disseminated toxoplasmosis is a potentially fatal complication in dogs receiving immunosuppressive therapy, particularly if multiple immunosuppressive drugs are used. Toxoplasmosis should be considered if signs of acute respiratory or hepatic disease develop, and diagnosis would rely on demonstration of organisms via cytology or PCR rather than a single time‐point serological assay. Abstract : Disseminated toxoplasmosis is a potentially fatal complication in dogs receiving immunosuppressive therapy, particularly if multiple immunosuppressive drugs are used. Toxoplasmosis should be considered if signs of acute respiratory or hepatic disease develop, and diagnosis would rely on demonstration of organisms via cytology or PCR rather than a single time‐point serological assay.